ARQ 087 inhibits FGFR signaling and rescues aberrant cell proliferation and differentiation in experimental models of craniosynostoses and chondrodysplasias caused by activating mutations in FGFR1, FGFR2 and FGFR3 - Balek, Lukas; Gudernova, Iva; Vesela, Iva; Hampl, Marek; Oralova, Veronika; Kunova Bosakova, Michaela; Varecha, Miroslav; Nemec, Pavel; Hall, Terence; Abbadessa, Giovanni; Hatch, Nan; Buchtova, Marcela; et al. (Bone, 2017)
Tyrosine kinase inhibitors are being developed for therapy of malignancies caused by oncogenic FGFR signaling but little is known about their effect in congenital chondrodysplasias or craniosynostoses that associate with activating FGFR mutations. Here, we investigated the effects of novel FGFR inhibitor, ARQ 087, in experimental models of aberrant FGFR3 signaling in cartilage. In cultured chondrocytes, ARQ 087 efficiently rescued all major effects of pathological FGFR3 activation, i.e. inhibition of chondrocyte proliferation, loss of extracellular matrix and induction of premature senescence. In ex vivo tibia organ cultures, ARQ 087 restored normal growth plate architecture and eliminated the suppressing FGFR3 effect on chondrocyte hypertrophic differentiation, suggesting that it targets the FGFR3 pathway specifically, i.e. without interference with other pro-growth pathways. Moreover, ARQ 087 inhibited activity of FGFR1 and FGFR2 mutants associated with Pfeiffer, Apert and Beare-Stevenson craniosynostoses, and rescued FGFR-driven excessive osteogenic differentiation in mouse mesenchymal micromass cultures or in ex vivo calvarial organ cultures. Our data warrant further development of ARQ 087 for clinical use in skeletal disorders caused by activating FGFR mutations.
Keywords: bezbuněčný systém; mutace; aniliny; receptory fibroblastových růstových faktorů; Cell Proliferation; Cell-Free System; Mice; Chickens; Organ Culture Techniques; Tibia; extracelulární matrix; Fibroblast Growth Factor 2; Cell Culture Techniques; kur domácí; orgánové kultury - kultivační techniky; Extracellular Matrix; Cellular Senescence; ARQ 087; FGFR; Chondrocytes; kraniosynostózy; Mutation; končetinové pupeny; Craniosynostosis; chinazoliny; Inhibitor; myši; signální transdukce; Rats; tibie; Quinazolines; Skeletal dysplasia; buněčná diferenciace; proliferace buněk; Aniline Compounds; Skull; Signal Transduction; fibroblastový růstový faktor 2; Cell Differentiation; zvířata; krysa rodu Rattus; Achondroplasia; Fibroblast growth factor receptor; chondrocyty; Craniosynostoses; buněčné kultury; lebka; Animals; Limb Buds; stárnutí buněk; Receptors, Fibroblast Growth Factor